Acupuncture improves exercise tolerance of patients with heart failure: a placebo-controlled pilot study - Kristen, Arnt; Schuhmacher, Boris; Strych, Kathrin; Loßnitzer, Dirk; Friederich, Hans-Christoph; Hilbel, Thomas; Haass, Markus; Katus, Hugo; Schneider, Antonius; Streitberger, Konrad; Backs, Johannes (Heart, 2010)
Background Congestive heart failure (CHF) is a complex clinical syndrome with autonomic dysbalance and increased plasma levels of inflammatory cytokines, which further worsen the syndrome. Experimental data have shown that stimulation of certain acupoints decreases autonomic dysbalance. - Objective To test the therapeutic potential of acupuncture for life-threatening diseases such as CHF. - Methods 17 stable patients with CHF (New York Heart Association class II-III, ejection fraction <40%) receiving optimised heart failure medication were randomised into a verum acupuncture (VA) and placebo acupuncture (PA) group. Cardiopulmonary function, heart rate variability and quality of life were explored. - Results No improvements of the cardiac ejection fraction or peak oxygen uptake were observed, but the ambulated 6 min walk distance was remarkably increased in the VA group (+32±7 m) but not the PA group (−1±11 m; p<0.01). Accordingly, post-exercise recovery after maximal exercise and the VE/VCO2 slope, a marker of ventilatory efficiency, were improved after VA but not PA. Furthermore, heart rate variability increased after VA, but decreased after PA. The ‘general health’ score and ‘body pain’ score of the quality-of-life questionnaire SF-36 tended to be improved after VA. - Conclusion Acupuncture may become an additional therapeutic strategy to improve the exercise tolerance of patients with CHF, potentially by improving skeletal muscle function.